A UV photodecomposition reactor for siloxane removal from biogas: Modeling aspects. (31st December 2018) - Divsalar, Alireza; Entesari, Nazanin; Dods, Matthew N.; Prosser, Richard W.; Egolfopoulos, Fokion N.; Tsotsis, Theodore T.
Highlights: A UV photodecomposition reactor (PhoR) studied for siloxane removal from biogas. 3D model developed validated with experiments. Model used for PhoR design/scale-up. Abstract: The goal of this research was to develop a model for a UV photodecomposition reactor (PhoR), which is used for the removal of trace siloxane impurities from biogas. The model properly accounts for the phenomena taking place inside the reactor, including fluid flow, mass and heat transfer, the transmission of UV radiation, and the photodecomposition reaction. Lab-scale experimental data were used to experimentally validate the model, and to also provide a "proof-of-concept" of the proposed PhoR technology prior to its field-testing at a real landfill site. The model was then utilized in the design of the experimental system used in the field-testing component of this study. Two reactor configurations were modeled: In the first configuration (termed PhoRI), the UV lamps are not in direct contact with the biogas, whereas in the second one (PhoRII), the lamps are placed in direct contact with the biogas stream. The PhoRII configuration is substantially more efficient for siloxane degradation, but concerns exist about the long-term robustness of the UV lamps in such an environment. The same model also presently finds use for further process design and scale-up, and in the preliminary technical and economic analysis (TEA) of the PhoR technology.